Penilaian Penggunaan Antibiotik pada Pasien Infeksi Saluran Pernapasan Akut Berdasarkan Indikator Penggunaan Obat Rasional di Puskesmas Teluk Merbau - Lilik Septiana; Darwin Syamsul; Ziza Putri Aisyia Fauzi; Cut Intan Annisa Cut Intan Annisa Puteri; Ferina Septiani Damanik (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Acute respiratory infections (ARIs) remain one of the leading causes of morbidity worldwide and contribute substantially to outpatient visits in primary healthcare facilities. Inappropriate antibiotic use in ARI management may accelerate antimicrobial resistance, a major global public health concern. Therefore, monitoring antibiotic utilization through Rational Drug Use (RDU) indicators is essential to promote appropriate prescribing practices. This study aimed to evaluate antibiotic prescribing patterns and assess compliance with Rational Drug Use indicators among ARI patients at Teluk Merbau Primary Health Care Center. A retrospective descriptive cross-sectional study was conducted using prescription records of patients diagnosed with ARIs from January to December 2022. Total sampling was applied, and all eligible prescriptions were included in the analysis. Data were analyzed descriptively using frequencies and percentages based on the Rational Drug Use indicators established by the Indonesian Ministry of Health. A total of 261 ARI prescriptions were analyzed. Female patients accounted for 55.94% of cases, while adults represented the largest age group (62.07%). Among all prescriptions, 90 contained antibiotics. Amoxicillin was the most frequently prescribed antibiotic (56.13%), followed by cefixime (18.33%), ciprofloxacin (11.83%), cefadroxil (10.10%), cotrimoxazole (2.02%), and metronidazole (1.59%). The proportion of antibiotic prescribing was 26.97%, exceeding the national RDU target of less than 20%. Antibiotic prescribing among ARI patients at Teluk Merbau Primary Health Care Center exceeded the recommended RDU indicator. Continuous monitoring, adherence to clinical guidelines, and implementation of antimicrobial stewardship programs are necessary to promote rational antibiotic use.